Utilização de blocos multinutricionais em diferentes sistemas de produção para cordeiros no semiárido brasileiro. - Almeida, Gabriel Henrique Oliveira (2019)
Two trials were carried out in different production systems (confined in feedlot and field pasture) using supplements for sheep in periods of food shortage in the semiarid region of Paraíba state. In the first study, the effect of molasses levels in the multinutrient blocks on the intake, performance, blood parameters and economic indicators in the diet of feedlot lambs was evaluated. Twenty-four Santa Inês lambs aged 4 to 5 months and 28.9 ± 3.67 kg of initial body weight were randomly assigned to four treatments with 6 lambs per treatment. Treatments consisted of levels of molasses, based on dry matter, in the composition of multinutrient blocks (200, 250, 300, 350 g / kg DM). The hardness of multinutrient blocks decreased linearly (P <0.05) with the increase of molasses in its composition. Molasses levels did not influence total CMS, forage, blocks and nutrient intake (P> 0.05), except for ether extract (P <0.05). The total weight gain and average daily gain of the animals presented negative linear effect (P <0.05) with the increase of molasses level in the multinutrient blocks, however, the conversion and feed efficiency were not influenced (P> 0.05). Molasses level altered blood glucose (P <0.05), but had no influence on the evaluation time (P> 0.05). Blood urea was influenced by treatment and evaluation times (P <0.05), but there was no interaction between treatments x evaluation time (P> 0.05). Serum creatinine was influenced by molasses levels in the blocks (P <0.05). Gross profit margin decreased as molasses level in the multinutrient blocks increased. In this study, it was observed that 200 g / kg DM of sugarcane molasses in the multinutrient block promoted the best performance for Santa Inês lambs without interfering with food intake and was more economically and biologically viable. In the second experiment, the objective of this study was to evaluate the effects of different types of supplementation for Dorper × Santa Inês crossbred lambs grazing Aruana (Megathyrsus maximus cv. Aruana) grazing in the dry-water transition period on intake, weight gain, ingestive behavior and economic indicators. In a completely randomized design, thirty male Dorper × Santa Inês crossbred lambs, 4 to 5 months old and 22.04 ± 1.69 kg of initial body weight were distributed in three treatments with 10 repetitions (T1 - Sal mineral; T2 - Multiple Mix; T3 xviii - Multinutrient Block). Total dry matter intake did not differ between treatments (P> 0.05), however, crude protein intake and water consumption were higher (P <0.05) for animals supplemented with multinutrient blocks. There was no difference for mean lamb weight gain (P> 0.05). Animals that received mineral mix and multiple mix spent more time grazing (P <0.05) than animals that received multinutrient blocks, consequently, spent less time with supplementation (P <0.05). Leisure time differed between supplement types (P <0.05) and for the three treatments, rumination time was equal (P> 0.05). According to economic indicators, there was an increase of 92% in gross margin for diet with mineral mixture when compared to lambs supplemented with multinutrient blocks and 57.5% in relation to the multiple mixture. The type of mineral supplementation can influence crude protein intake and modify the ingestive behavior of Dorper × Santa Inês lambs without affecting their performance during the dry-water transition period under Aruana (Megathyrsus maximus cv. Aruana) grazing. Supplemental diets for lambs with mineral mixture in this experimental condition was more economically viable.